The voice of Mexican small-scale fishers in times of COVID-19: Impacts, responses, and digital divide. (September 2021) - Lopez-Ercilla, Ines; Espinosa-Romero, Maria Jose; Fernandez Rivera-Melo, Francisco J.; Fulton, Stuart; Fernández, Rebeca; Torre, Jorge; Acevedo-Rosas, Araceli; Hernández-Velasco, Arturo J.; Amador, Imelda
Abstract: The COVID-19 pandemic has dramatically, quickly, and extensively affected fisheries, the effects of which have yet to be quantified globally, although some efforts have already been made locally and regionally. This study provides insights regarding the impacts of the pandemic in Mexican small-scale fisheries, explores community responses and digital divide. A total of 1493 interviews were conducted, and a social media analysis that reviewed 9079 posts from April to December 2020 was performed. The results show large socio-economic and environmental impacts (e.g. 89% of the markets closed in April, and 72% of respondents perceived an increase in the amount of solid waste). Women have faced increased inequalities when accessing fishing resources or healthcare. Responses have been varied and include closing communities, and fishing organizations distributing emergency funds. Fishers relate feeling very or moderately comfortable with technology and have spent more time using digital platforms during the pandemic than before. While the effects are still unfolding, there is an urgent need to breach the digital divide to guarantee equal opportunities for all. Efforts are needed to ensure that the most vulnerable groups (e.g. women, indigenous people, and elderly individuals) are not excluded from opportunities to access, use or manage resources, including technology. This global crisis may also bring opportunities for adaptation and the implementation of local solutions (e.g. reducing the fishing effort for high-value products), to prepare for future shocks. The findings in this study serve to promote development strategies that build resilience in fishing communities for healthier oceans. Highlights: Mexican fishers experienced a massive shut down at the start of the pandemic. Organizational resources were not in place to effectively respond to the pandemic. Community-based solutions focused on developing local markets and implementating sanitary measures. Women are less able to access fishing resources and healthcare compared to men. The digital divide increases inequities especially for vulnerable groups (women, elder); combined digital-analogical approaches are needed.